Gene-environment interaction and oxidative stress in cardiovascular disease - Stephens, Jeffrey (Henry Stewart Talks, 2008)
Oxidative stress: a risk factor for CVD, Biochemical markers of oxidative stress, Genetic determinants of oxidative stress: examples, Examples of gene-environment interaction in determining oxidative stress and CVD, Other gene variants and oxidative stress
Archived at 2021/02/25